Analisis Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen pada Pasar Tradisional di Malang - Wiwik Retnaningsih (Universitas Negeri Surabaya, 2018)
This research attempt to recognize what facts which influencing a consumer buying in traditional market in Malang city. Since economic crises clear away Indonesia emerge street merchants trading, merchants who trade in traditional markets. Their number bigger and bigger get along with Indonesia economic drop and stumble. From observation result indicating that those merchants able to survive until now. It mean that there are consumer who their market segment. Therefore reason above try to examined what any factors which caused consumers taking decision through traditional market as one of place to fulfil their needs. From the result of the research can be explained that consumer choose product which sold in traditional market consists of nine factor components comprise rotation yield from twenty five variables that are social solidarity factor, promotion, purchase service, guarantee and product quality. This research using factor analysis as analysis with SPSS Program.